Handbook of Composite Reinforcements. - Lee, Stuart M. (John Wiley & Sons, 1992)
Annotation This comprehensive single volume handbook covers every aspect of reinforcement science, from hands-on subjects, such as manual 'lay-up' processing, to theoretical discussions concerning rheology and modeling. Taken from the recently published six volume International Encyclopedia of Composites, this reference volume offers scholarly and practical knowledge of distinguished industry-experts, academics, and government researchers in one accessible and informative handbook. Fibers, processes, and composite reinforcement types, as well as relevant miscellaneous subjects such as property relationships, manufacturing, hybrid reinforcements, and modeling are given detailed treatment. Engineers, materials scientists, and technologists will find the Composite Reinforcement Handbook an invaluable tool.
Keywords: Composite materials.; elektronické knihy; electronic books